Konseling Kognitif Perilaku Dengan Teknik Bermain Peran Untuk Meningkatkan Self Change - Jannah, Nikmatul; Suranata, Kadek; Dharsana, I Ketut (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the influence of cognitive counseling behavior with role playing techniques to improve self-change students in the class X IPS 1 SMA Negeri 4 Singaraja. The type of this research is quasi experiment (Quasi experiment) The sample of this research is determined by using Nonequivalent Control Group Design technique with the number of 60 students 30 students who become experimental group and 30 control group students. The analytical method used is (1) rasch analysis to transmit data in logit scale, (2) t-brunning to calculate the effectiveness test of cognitive behavioral counseling with role playing technique to self-change student, (3) t-test to know difference of influence between counseling cognitive behavior with role playing techniques with classical guidance to self-change. The results showed the influence of cognitive counseling behavior with role playing technique to increase self-change value t_hitung> t_tabel (23,63> 2.04). So there are differences in self-change among students who received treatment and who did not get treatment of cognitive counseling behavior technique role play value t_hitung> t_tabel (0,02 <2,04). Effect Size which gets treatment is worth 20,79 whereas there is difference of Effect Size which do not get treatment with value 0.00048. Keywords: Cognitive behavioral counseling, role playing techniques, self-change